Report of the deputation to Metlakatla [electronic resource] : (General Touch and the Rev. W.R. Blackett). - Church Missionary Society.; Touch, J. G.; Blackett, W. R. ([London? : s.n., 1886)
Letters signed: J.G. Touch W.R. Blackett. Caption title. At head of title: (Private.--For the use of the Committee). Church Missionary Society. Electronic reproduction. Mode of access: Internet. 44